Minor Oral Surgery and Dental Extraction Procedures Management of Patients with Antithrombotic Drugs Administration: Manajemen Prosedur Bedah Mulut Minor dan Ekstraksi Gigi pada Pasien dengan Pemberian Obat Antitrombotik - Dwi Riski Saputra (Dentika: Dental Journal, 2020)
Patients who are undergoing antithrombotic drugs therapy whether it was alone or in combination can increase the bleeding complications after performed minor oral surgery or tooth extraction. If the termination of using antithrombotic drugs to prevent bleeding isn’t right, it’ll trigger thrombosis. Therefore appropriate consideration is needed in the management of patients undergoing antithrombotic drug therapy that requires minor oral surgery or dental extraction. The purpose of this literature review is to examine management of minor oral surgery and dental extraction procedure in patients with antithrombotic drugs. Management of minor oral surgical procedures and tooth extraction in patients using antithrombotic drugs must be adjusted to the type of antithrombotic drugs used by the patient. Patients who use antithrombotic drugs are advised to undergo minor oral surgery or tooth extraction treatment in the morning or on weekends. Local hemostatic agent has been shown to be effective to stop bleeding locally on minor oral surgical procedure or tooth extraction in patients undergoing antithrombotic drug therapy alone or in combination.